PERAN MEDIA SOSIAL DALAM PEMBENTUKAN PERILAKU REMAJA - Tafsir Tambunan, Mhd; Rahma Harahap, Siti; Derajat Silaen, Mulkan (Penerbit Lafadz Jaya, 2025)
The role of social media in shaping adolescent behavior is an important issue to be studied in the context of current developments in communication technology. The purpose of this study is to analyze the positive and negative impacts of social media on adolescent behavior, as well as to understand the factors that influence the use of these platforms. The approach used is Virtual Ethnography, which allows observation of adolescent interaction behavior in cyberspace. The results of the study indicate that social media can increase access to information, creativity, and communication skills, but also has the potential to cause addiction, decreased mental health, and cyberbullying. Therefore, understanding the role of social media is very important for parents, educators, and policy makers to create an environment that supports positive adolescent growth in the digital world. This study is expected to provide useful insights in managing the use of social media among adolescents, so as to maximize the benefits obtained while minimizing the risks.